Inhibitory Effect of Cibenzoline on Na+/Ca2+ Exchange Current in Guinea-Pig Cardiac Ventricular Myocytes - Tomomi Yamakawa; Yasuhide Watanabe; Hiroshi Watanabe; Junko Kimura (Elsevier, 2012)
The effect of cibenzoline, a class I antiarrhythmic drug, on Na+/Ca2+ exchange current (INCX) was investigated using the patch-clamp method. Cibenzoline inhibited the bi-directional INCX in a concentration-dependent manner. The IC50 values of cibenzoline for the outward and inward components of INCX were 77 and 84 μM, respectively, with Hill coefficients of 1. Intracellular application of trypsin via the pipette solution did not change the inhibitory effect of cibenzoline. The inhibitory effect of cibenzoline on INCX at pHo 6.5 was smaller than those at pHo 7.4 and pHo 8.2. We conclude that cibenzoline inhibits INCX in supra-therapeutic concentrations. Keywords:: antiarrhythmic drug, cibenzoline, Na+/Ca2+ exchange (NCX)